Healing, Magic, and Mind : The Early Modern Finnish-Karelian Healing Tradition in Light of the Cognitive Science of Religion and Ritual Studies - Kohonen, Siria (Helsingin yliopisto, 2022)
This dissertation focuses on analysing the ways in which people in early modern Finland and Karelia encountered and interpreted their traditional healing practices and performances, and how they represented these interpretations in recollections and narratives that they told to folklore collectors. The Finnish-Karelian healing tradition was closely connected to a worldview in which otherworldly and supranormal influences were considered to be able to affect an individual’s health, and it included many magical and ritualistic performances. Earlier studies on the subject have mostly concentrated on the perspective of ritual specialists, whereas this study focuses on the perspective of the lay people. The material corpus analysed in the study comprises over 600 archive units from the Folklore Archive of Finnish Literature Society. These archive materials consist of recollections about traditional healing situations, incantation texts, and narratives about healers. The materials were collected via ethnographic interviews from all over Finland and Karelia between 1880 and 1939. Especially in the rural provinces, the period could be described as pre-industrial and early modern, since the consequences of modernization appeared rather late there. The theoretical background of the study combines the research fields of folklore studies, ritual studies, and the cognitive science of religion. In the analyses, the study focuses on cognitive theories about memory schemas and dual processing of the mind, medical theories about the placebo effect, and folkloristic performance theories. The research methods include contextualizing, schema analysis, and theory-based qualitative analysis. From a broader methodological perspective, the study aims to both understand and explain the studied phenomena. Via the analyses in three separate research articles, this study presents that the cognitive processes of the human mind have significantly guided the ways in which the healing tradition was interpreted and represented in recollections ...